2003
DOI: 10.1038/sj.onc.1206528
|View full text |Cite
|
Sign up to set email alerts
|

Integrations of the hepatitis B virus (HBV) and human papillomavirus (HPV) into the human telomerase reverse transcriptase (hTERT) gene in liver and cervical cancers

Abstract: Chronic infections with the hepatitis B virus (HBV) and high-risk human papillomaviruses (HPVs) are important risk factors for hepatocellular carcinoma (HCC) and cervical cancer (CC), respectively. HBV and HPV are DNA viruses that almost invariably integrate into the host genome in invasive tumors. The viral integration sites occur throughout the genome, leading to the presumption that there are no preferred sites of integration. A number of viral integrations have been shown to occur within the vicinity of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(147 citation statements)
references
References 32 publications
3
142
0
2
Order By: Relevance
“…Besides MYC, a number of genes, potentially involved in carcinogenesis, such as CEACAM5, FANCC (Wentzensen et al, 2002;Ferber et al, 2003b), TP63 (Wentzensen et al, 2002), TERT (Ferber et al, 2003a), MYOF, Ribosomal protein gene RPS27 (Klimov et al, 2002), MYCN (Sastre-Garau et al, 2000), NFIB (Ziegert et al, 2003), have also been found to correspond to targets for the insertion of HPV DNA. In spite of this diversity, only a few cases with an integration pattern compatible with a mechanism of insertional mutagenesis have been observed (Wentzensen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Besides MYC, a number of genes, potentially involved in carcinogenesis, such as CEACAM5, FANCC (Wentzensen et al, 2002;Ferber et al, 2003b), TP63 (Wentzensen et al, 2002), TERT (Ferber et al, 2003a), MYOF, Ribosomal protein gene RPS27 (Klimov et al, 2002), MYCN (Sastre-Garau et al, 2000), NFIB (Ziegert et al, 2003), have also been found to correspond to targets for the insertion of HPV DNA. In spite of this diversity, only a few cases with an integration pattern compatible with a mechanism of insertional mutagenesis have been observed (Wentzensen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, we have demonstrated that (1) HBV insertion into cellular genes is in fact frequent (around 70%) and (2) HBV integration can occur in genes encoding for proteins with a fundamental role in the control of cell signaling, proliferation and viability (Figure 2) (Horikawa and Barrett, 2001;Ferber et al, 2003;Paterlini-Brechot et al, 2003;Murakami et al, 2005;Tamori et al, 2005). Most importantly, our work, combined with recent investigations from other groups, has also led to demonstrate that the telomerase and mixed lineage leukemia encoding genes are in fact targeted by HBV in different HBV-related HCCs, thus suggesting common pathways in HBV-related carcinogenesis (Horikawa and Barrett, 2001;Ferber et al, 2003;Paterlini-Brechot et al, 2003;Murakami et al, 2005;Tamori et al, 2005). Figure 2 The insertion of HBV genome in cellular genes frequently targets genes that regulate key cellular pathways.…”
Section: Hbv-related Hcc D Kremsdorf Et Almentioning
confidence: 99%
“…Second, insertional mutations have been described in which HBV integration at specific sites activates endogenous genes such as retinoic acid b-receptor (Dejean et al, 1986), cyclin A (Wang et al, 1990) and mevalonate kinase (Graef et al, 1994). More recently, 15 new genes were found to be altered by an HBV integration in tumors, suggesting that viral integration in the vicinity of genes controlling cell proliferation, viability and differentiation is a mechanism frequently involved in HBV hepatocarcinogenesis (Ferber et al, 2003;Horikawa and Barrett, 2003;Paterlini-Brechot et al, 2003). All of these integration events are unique, except for the human telomerase reverse transcriptase (hTERT) and the inositol 1,4,5-triphosphate receptor (IPR) genes that have been observed to have site-specific HBV integrations in independent tumors (Ferber et al, 2003;Horikawa and Barrett, 2003;Paterlini-Brechot et al, 2003).…”
Section: Genetic Alterations and Hepatitis B Virus Infectionmentioning
confidence: 99%